Livestock Environment VI, Proceedings of the 6th International Symposium 2001
DOI: 10.13031/2013.7131
|View full text |Cite
|
Sign up to set email alerts
|

Oil Sprinkling and Dietary Manipulation to Reduce Odour and Gas Emissions from Swine Buildings - Laboratory Scale Experiment

Abstract: The project evaluated the impact of four canola oil application rates (0, 10, 20 and 30 ml/m 2-day) combined with three specific diet formulations (18% protein, 16% protein and 16% protein plus fermentable carbohydrates) on odour and gas emissions from grower-finisher swine buildings. The strategy of combining engineering and nutrition expertise is expected to reduce the potential impact of the pig barn on its surroundings. An experimental setup of twelve independent chambers each housing four castrated pigs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previously, Banskota et al [ 17 ] reported that the oil/water spray technique showed a major impact on pig farm dust control. Similarly, Godbout et al [ 18 ] reported that canola oil sprinkling 2 times per day reduced 27% hydrogen sulfide and 30% ammonia concentrations in the piggery barn. Moreover, Rahman and Borhan [ 19 ] noted that the addition of microorganisms directly to the manure of anaerobic dairy lagoons reduces the solids and nutrient content.…”
Section: Introductionmentioning
confidence: 94%
“…Previously, Banskota et al [ 17 ] reported that the oil/water spray technique showed a major impact on pig farm dust control. Similarly, Godbout et al [ 18 ] reported that canola oil sprinkling 2 times per day reduced 27% hydrogen sulfide and 30% ammonia concentrations in the piggery barn. Moreover, Rahman and Borhan [ 19 ] noted that the addition of microorganisms directly to the manure of anaerobic dairy lagoons reduces the solids and nutrient content.…”
Section: Introductionmentioning
confidence: 94%